Software Project Planning Through Simulation of Entire Project's Problem-Space - Dayani, Moshe; Gelbard, Roy (International journal of information technology project management, 2017)
The current research has two main objectives: 1) Integration of the system analyst's products together with the project manager's work, via handshaking of software tools used for these tasks (Software modeling tools, Project management tools, as well as Word and Excel files). 2) Simulation of the entire project's problem space subject to organization's policy and constraints in order to achieve best project planning in the given situation. For this purpose, a rule-based system, developed in this study, utilizes a simulation of entire project's problem-space, which is a Cartesian product composed of all system elements (as defined in the software modeling tool), and organization's policy, preferences and constraints, via a specific user interface (see Figure 1). Then the project manager can choose, by simple filtering, the appropriate planning, and the Gantt-chart and all plans' details are automatically exported to the Project Management tool.